Perlindungan Hukum Bagi Korban Pembegalan Yang Tidak Sengaja Membunuh Pelaku Begal - Soetrisno Soetrisno (Universitas Palangka Raya, 2024)
This article aims to analyze the legal protection for victims of mugging who unintentionally kill the mugger. The research method used is a literature review by collecting data from relevant research journals published between 2019-2024. The results show that victims of mugging who unintentionally kill the mugger can be protected by law on the grounds of self-defense. However, further investigation is needed to prove that the action was indeed carried out as an act of self-defense. In conclusion, the law in Indonesia needs to provide more comprehensive protection for victims of crime, including victims of mugging, so that they are not afraid to report the crimes that have befallen them.